Effects of Group Training on Maternal Knowledge and Attitude toward Sexual Health Education to 12 to 14 Years old Boys - Raha Rousta; Khadijah Mirzaii; Negar Asghari Pour; Azadeh Saki (Mashhad University of Medical Sciences, 2019)
Background & aim: Sexual health education is an important part of health promotion services. Families including mothers have a major role  in boys' sexual education so that they have to be equipped with enough knowledge regarding their young teens. The present study aimed to investigate the effect of group training on maternal knowledge and attitude toward sexual health education to boys within the age range of 12-14 years old Methods: This randomized controlled trial was carried out on a total of 90 mothers with young teens in Mashhad in 2016. They were randomly divided into intervention (n=46) and control (n=44) groups. The data were collected using a demographic and a self-structured questionnaire for maternal knowledge and attitude. The intervention group received four training sessions once a week and the control group did not receive any training. The outcome variables were measured 15 days after the intervention and were analyzed using the Chi-square, Fisher's exact, Kruskal-Wallis, Mann-Whitney U, and Wilcoxon signed-rank tests, as well as the independent and paired t-test. Results: There was no significant difference between two groups before intervention (P>0.05). However, a significant difference was seen between the two groups in terms of differences in the scores of knowledge (P<0.001)  and attitude (P<0.001)  at the beginning and end of the study . Conclusion: Group training can result in significant changes in maternal knowledge and attitude with regard to the young teens' sexual health education.